2023
DOI: 10.3389/fimmu.2023.1094464
|View full text |Cite
|
Sign up to set email alerts
|

Targeting β-glucans, vital components of the Pneumocystis cell wall

Abstract: β-glucan is the most abundant polysaccharide in the cell wall of Pneumocystis jirovecii, which has attracted extensive attention because of its unique immunobiological characteristics. β-glucan binds to various cell surface receptors, which produces an inflammatory response and accounts for its immune effects. A deeper comprehension of the processes by Pneumocystis β-glucan recognizes its receptors, activates related signaling pathways, and regulates immunity as required. Such understanding will provide a basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…These macromolecules are formed through the union of smaller monosaccharides, via glycosidic bonds, and play a fundamental role in the structure of the cell wall of the organisms in which they are present. Glucans are subject to the action of various enzymes responsible for generating the bonds that join the smaller units of monosaccharides and that participate in the construction and conformation of the polysaccharide [ 39 ]. This is an important factor since various studies have described how the chemical structure of glucans is directly related to their biological activity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These macromolecules are formed through the union of smaller monosaccharides, via glycosidic bonds, and play a fundamental role in the structure of the cell wall of the organisms in which they are present. Glucans are subject to the action of various enzymes responsible for generating the bonds that join the smaller units of monosaccharides and that participate in the construction and conformation of the polysaccharide [ 39 ]. This is an important factor since various studies have described how the chemical structure of glucans is directly related to their biological activity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…39 The early immune system's targeting and killing of tumor cells depend on dendritic cells (DCs) producing type I interferons (IFNs) and recruiting CD8 + T cells, while the STING pathway plays a unique role in this critical step of anti-tumor immunity by attracting CD8 + T cells to the TME. 40 Moreover, the cGAS-STING pathway can initiate the synthesis of antiviral cytokines belonging to the type I interferon family, leading to the induction of hundreds of interferon-stimulated genes (ISGs) that possess diverse antiviral activities. 41 Mn 2+ act as potent activators of cGAS, triggering cells to produce type I IFNs and cytokines even without any infection.…”
Section: Immune Defense Functionmentioning
confidence: 99%
“…Soyasapogenol B, classified as a triterpenoid, has demonstrated a diverse range of biological functions through experimental evidence, including the ability to reduce inflammation, alleviate allergies, protect the heart, regulate metabolism and blood sugar levels, as well as exhibit anticancer effects (Omar et al, 2020). 25-Hydroxycholesterol participated in cholesterol metabolism, possessing unique biosynthetic pathways and structures, while also being involved in autophagy and inflammatory responses by regulating signaling pathways (Zhang, Zhu, et al, 2023). Guo et al (2020) from ethanol-induced lipid accumulation mouse experiments found that Rosmarinic acid had a regulatory effect on ethanol-induced inflammation by decreasing the levels of tumor necrosis factor-α (TNF-α).…”
Section: Go and Kegg Enrichment Analysis Of Overlapping Targetsmentioning
confidence: 99%